A Review :Drug–Gene Interactions in Precision Cancer Therapy: Emerging Roles of Immunotherapy, Suicide Genes, and Molecular Editing Tools - Maytham Oleiwia , Bassma; Jassim Manshad , Maha; Naser Abbas, Saly; Habeeb Obaid , Nada (Pure Sciences International Journal of Kerbala, 2026)
Cancer remains one of the major threats to human fitness, and although there are many treatments available to address this problem, conventional treatments including radiotherapy and chemotherapy have significant adverse effects and are by no means ideal. Gene therapy is a newly developed treatment modality that provides superior targeting with fewer adverse effects than conventional treatments. To change the expression of gene products, foreign genetic material is injected into the host tissue during gene therapy. Gene therapy provides the opportunity to influence the course of many diseases. Therefore, reliable and safe gene products and vector application coupled with advanced biotechnology will be crucial in the treatment of various diseases in the future. Gene therapy is a treatment strategy of opportunity that has been extensively studied recently. The therapeutic genes are implanted at the specified site. Cell or tissue specific to the majority of tumors these compounds have the ability to either induce cell death or inhibit the rate of cell proliferation. Of most types of cancer. Many viral and non-viral genes and vectors are being used in investigations because this treatment uses unique approaches that involve either silencing inactivated or unwanted genes or activating recovery genes. Activation of tumor suppressor genes is a crucial mechanism that helps control the growth of tumors and suppress them, and controls the function of oncogenes and inhibits their activation. Our explanation in this article covers gene therapy, methods of treating most tumors using genes, the use of approved genetic drugs to treat most malignant tumors, and the future of gene therapy for cancer. . Gene therapy no longer meets the criteria to completely replace conventional treatments. But with a deeper understanding of the process behind cancer treatment, one can choose the optimal course of action and target for future gene therapy, either alone or in combination with other therapies.